DESAIN PRODUK MAKANAN LOKAL BERBASIS INDUSTRI KECIL MENENGAH: Ali Alamsyah Kusumadianata, Maria Fitriah - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2017)
Increasing the number of local food businesses in the form of products that are worth selling the industry isincreasing in quantity and quality. Bogor is one of the tourist destinations with local food identity. Thereforethe research has purposes (1). Describe the visual communication design of food label of small and mediumindustry circulating in Bogor city. (2). Describe the aspects of small and medium industry food labels thathave been adopted by small and medium-sized industries. (3). Analyze consumer buying interest in small andmedium industries. The research method uses a qualitative approach where the analysis used is the case andthe semantics of the product are visually observed. The results show that the local product has a culturalaesthetic value that is able to lift tourism by generating visual communication design, by showing the labelinformation aspects of the production contained on the packaging. It can be able to attribute tourist visits inconsuming local products by improving the quality of packaging product design.